Contested Truths Over COVID-19 in East Africa : Examining Opposition to Public Health Measures in Tanzania and Uganda - Lee, Jia Hui; Meek, Laura; Katumusiime, Jacob (African Studies Review, 2023)
The comparative analysis of three “contested truths” around COVID-19 in East Africa demonstrates that knowledge is a product of knotted, uneven, and disputed epistemological practices tied to structures of power. Lee, Meek, and Katumusiime examine: (1) the construction of a pan-African skepticism of COVID-19 that drew on anti-imperialist discourses; (2) social media posts through which Tanzanian digital publics critically evaluated steam inhalation as an alternative therapeutic for COVID-19; and (3) the resistance by many Ugandans to complying with public health measures such as lockdowns. “Contested truths” is used as an analytical framework to center the specificity and situatedness of truth-making in East Africa during the COVID-19 pandemic.
Keywords: COVID-19; Epistemology; Global Health; Tanzania; Uganda; digital publics; decoloniality; Truth; civil society; Protest